Peningkatan Hasil Belajar Siswa pada Pembelajaran IPA dengan Model Problem Based Learning di Sekolah Dasar - Stivani Meila Tasha; Syamsu Arlis; Zainarlis Zainarlis (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research was to improve of student learning outcomes in learning the IPA with the model of Problem Based Learning. This research is a Research Action class, using qualitative and quantitative approach. In each cycle includes four stages, namely planning, implementation, observation and reflection. Implemented in 2 cycle, consists of 3 meeting. The subject in this research is the teacher and the students of classes V SDN 13 Parit Putus Agam Regency. Research instruments namely observation sheet and sheet test. The results showed an increase in: a) lesson plan (RPP) cycle I percentage value of 75% (C), in cycle II 96.4% (SB), b) implementation learning (aspects of teacher) I cycle average value of 73.2% (C), in cycle II 96.4% (SB), c) implementation at the student aspect of the average value of the cycle I 71.6% (C), in cycle II 93.1% (SB), d) student learning outcomes on cycle I average 75.9 (C), an increase of 86 in cycle II (SB). Can be conluded that Problem Based Learning (PBL) can improve student learning outcomes in learning the IPA in class V SDN 13 Parit Putus Agam Regency.Keywords: Learning Outcomes, Science, Model Problem Based Learning (PBL).